2005
DOI: 10.1097/01.pec.0000181426.25342.a9
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Closed Head Injuries Treated in an Observation Unit

Abstract: The vast majority (96%) of pediatric OU patients with CHI such as small intracranial hematomas, skull fractures, and concussions were discharged safely within 24 hours without serious complications. The presence of a basilar skull fracture, head laceration, and the need for ED IV fluids were associated with increased risk of UIA. OU admission is an efficient and effective management setting for children with stable intracranial pathology, skull fractures, and concussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 5 publications
(8 reference statements)
3
33
0
2
Order By: Relevance
“…24 Similar to prior studies, 4,15,[25][26][27][28][29][30] our results also indicate that return visits and readmissions following observation are uncommon events. Our findings can serve as initial benchmarks for condition-specific outcomes for pediatric observation care.…”
Section: Discussionsupporting
confidence: 78%
“…24 Similar to prior studies, 4,15,[25][26][27][28][29][30] our results also indicate that return visits and readmissions following observation are uncommon events. Our findings can serve as initial benchmarks for condition-specific outcomes for pediatric observation care.…”
Section: Discussionsupporting
confidence: 78%
“…ED-based OUs, which often provide operationally and physically distinct care to observation patients, have been touted as cost-effective alternatives to inpatient care, [18][19][20] resulting in fewer admissions and reductions in length of stay 19,20 without a resultant increase in return EDvisits or readmissions. [21][22][23] Research is needed to determine the patient-level outcomes for short-stay patients in the variety of available treatment settings (eg, physically or operationally distinct OUs and virtual observation), and to evaluate these outcomes in comparison to results published from designated OUs. The operationally and physically distinct features of a designated OU may be required to realize the benefits of observation attributed to individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…18 Among patients with closed head injuries treated in an OU in a pediatric level 1 trauma center, patients with basilar skull fracture, head laceration, or the need for intravenous fluids were more likely to need inpatient admission after OU management. 27 A recent study at a major children' s hospital revealed use of certain resources, including intravenous fluids and medications, cardiorespiratory monitoring, respiratory therapy, subspecialty consultation, and oxygen, were associated with hospitalization. 28 The diagnoses most commonly leading to hospitalization included asthma, adenitis, cellulitis, bronchiolitis, and the presence of esophageal foreign bodies.…”
Section: Measuring and Ensuring Quality Of Care In Ousmentioning
confidence: 99%